2017
DOI: 10.1364/oe.25.001605
|View full text |Cite
|
Sign up to set email alerts
|

High-speed, two-dimensional synchrotron white-beam x-ray radiography of spray breakup and atomization

Abstract: High-speed, two-dimensional synchrotron x-ray radiography and phase-contrast imaging are demonstrated in propulsion sprays. Measurements are performed at the 7-BM beamline at the Advanced Photon Source user facility at Argonne National Laboratory using a recently developed broadband x-ray white beam. This novel enhancement allows for high speed, high fidelity x-ray imaging for the community at large. Quantitative path-integrated liquid distributions and spatio-temporal dynamics of the sprays were imaged with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…Synchrotron X-ray radiography of the atomizer and resulting spray was performed in the Advance Photon Source (APS) at Argonne National Laboratory, 7-BM beamline [Kastengren et al, 2012]. It provides high-intensity broadband X-rays that can be used for 2D radiographic imaging with microsecond or sub-microsecond time resolution [Halls et al, 2017]. Such radiography is often referred to as white beam imaging because the energy spectra of the illuminating beam is distributed over a broadband of wavelengths.…”
Section: High-speed X-ray Imagingmentioning
confidence: 99%
“…Synchrotron X-ray radiography of the atomizer and resulting spray was performed in the Advance Photon Source (APS) at Argonne National Laboratory, 7-BM beamline [Kastengren et al, 2012]. It provides high-intensity broadband X-rays that can be used for 2D radiographic imaging with microsecond or sub-microsecond time resolution [Halls et al, 2017]. Such radiography is often referred to as white beam imaging because the energy spectra of the illuminating beam is distributed over a broadband of wavelengths.…”
Section: High-speed X-ray Imagingmentioning
confidence: 99%
“…Synchrotron X-ray sources can also provide high intensity broadband X-rays that can be used for 2D radiographic imaging with microsecond or sub-microsecond time resolution (Halls et al, 2017b). It is called white beam radiography because the high intensity continuous wave beam is composed of a range of energies (wavelengths) like that shown in Figure 2, similar to white light being composed of a range of wavelengths in the visible spectrum.…”
Section: White Beam Radiographymentioning
confidence: 99%
“…As the emission is in the x-ray regime, it is not attenuated significantly by scattering from phase interfaces and has shown to be useful diagnostic Finally, x-ray imaging has also seen recent development and advancements in both tube sources and at the APS -7BM. [12][13][14][15][16][17] Many previous efforts utilizing x-ray imaging utilized phase contrast imaging and tube sources, though recent facility upgrades have has made imaging at the APS -7BM possible.…”
Section: -7mentioning
confidence: 99%
“…In the research campaign, a recently developed two-dimensional x-ray radiography technique was applied to the study of transient fluid structure during spray atomization at speeds of 120 kHz, as fully detailed in Halls et al 17 Radiographic images collected also revealed complex fluid structure within the primary atomization region of the spray, such as hollow droplets and stable mixed phase regions. An example plot is shown in Fig.…”
mentioning
confidence: 99%